Emerging Trends in the Social and Behavioral Sciences 2015
DOI: 10.1002/9781118900772.etrds0355
|View full text |Cite
|
Sign up to set email alerts
|

The Underrepresentation of Women in Elective Office

Abstract: Despite the inroads women have made in American politics in recent decades, women still hold far fewer elective offices than men. This raises the question of why women fall short in this important mode of political engagement. Early research on this question emphasized the obstacles created by gender socialization, women's underrepresentation in the professions most likely to produce candidates, and women's family and household responsibilities. Scholars have also found that some voters use gender stereotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…If these barriers significantly undermined women’s chances of winning, we would expect to observe that women raise less money and/or win at lower rates than men. However, female candidates fundraise similar amounts as male candidates, a trend that holds across types of office and stages of elections (Adams & Schreiber, 2011; Anzia, 2015; Seltzer, Newman, & Leighton, 1997; Thomas & Wilcox, 2014). Research has also consistently demonstrated that women are equally or more likely to win than men, including in judicial elections.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…If these barriers significantly undermined women’s chances of winning, we would expect to observe that women raise less money and/or win at lower rates than men. However, female candidates fundraise similar amounts as male candidates, a trend that holds across types of office and stages of elections (Adams & Schreiber, 2011; Anzia, 2015; Seltzer, Newman, & Leighton, 1997; Thomas & Wilcox, 2014). Research has also consistently demonstrated that women are equally or more likely to win than men, including in judicial elections.…”
Section: Theoretical Foundationsmentioning
confidence: 99%